Human capital and genetic diversity - Sequeira, T. N.; Santos, M.; Ferreira-Lopes, A. (Eurasian Economic Review, 2019)
This paper investigates the relationship between human capital and the ancestral genetic diversity of populations. A simple model highlights a new channel through which genetic diversity can affect development: human capital. Additionally, empirical evidence of an unconditional hump-shaped relationship between genetic diversity and human capital is documented. This relationship decreases statistical significance when other deeply rooted determinants of human capital are taken into account. However, we found some significantly positive (linear) effects of genetic diversity. Thus, if there is a relationship between genetic diversity and human capital, this relationship tends to be positive: more genetic diversity is beneficial to human capital.